Questões de avaliação de design de um curso de inglês online - Wadt, Maria Paula Salvador (2002)
This dissertation aims at analyzing the design developed in the courseware WebCT of a unit in the online module Listening Comprehension I intended for English teachers of state schools, through the students reactions and attitudes while taking the course, in order to verify inadequacies in the design that influenced the learning processes originally expected to the course. The main theoretical underpinning for the research is provided by studies in distance learning, in the theories of instructional design, especially supported by Duchastel (1997); Khan (1997); Reigeluth (1999); Horton (2000); among others. The research questions were the following: 1) How was the design process of the unit Listening to a Documentary? 2) What were the basic characteristics of the original proposal? 3) How was the course implementation according to the original proposal? 4) What aspects of the design were well evaluated by a successful implementation? 5) What aspects of the design were badly evaluated by a problematic implementation? 6) What problematic aspects of the design had alterations during the course implementation? 7) What were the basis/precepts used for the alterations? The data collected for the study were taken from notes of the designer during the development process of the course design and from the records of the course implementation. Firstly, the study describes the design of the module evaluated; then it presents an interpretive analysis of data collected during the implementation of the course concerning to the students attitudes in respect to what was proposed in the design. The findings point to design inadequacies responsible to difficulties in task accomplishment by the students due to the following problems derived from the design: a) inadequate language of instructions; b) lack of explicit pedagogical objective for the chat sessions; c) inappropriate choice of courseware tool; d) lack of suggestion for estimated time spent in the tasks; e) inadequate graphic elaboration. The results also suggest an upgrade of the original design aiming at optimizing the link between course design and a successful implementation